A four-year simulation of soil aquifer treatment using columns filled with San Gabriel Valley sand. (1st November 2018) - Trussell, Bryan; Trussell, Shane; Qu, Yan; Gerringer, Fred; Stanczak, Sangam; Venezia, Teresa; Monroy, Israel; Bacaro, Fernanda; Trussell, Rhodes
Abstract: Two column pairs filled with 3.05-m of a sandy soil from the Upper San Gabriel Valley were operated for a period of four and ½ years on municipal effluent from the San Jose Creek Water Reclamation Plant operated by the Sanitation Districts of Los Angeles County (LACSD). One column pair was fed filtered, chlorinated effluent (tertiary effluent) for the entire period. The other pair was fed ozonated secondary effluent for 8-mo, ozonated secondary effluent filtered through biological activated carbon (O3 /BAC) for 7-mo and tertiary effluent for 38-mo. Each column pair was operated in series, where the first column was operated for a shorter residence time and the second column for a longer residence time. Residence times tested were 5-d, 28-d, 30-d, 58-d, 60-d, 150-d and 180-d. For the last 38-mo, both pairs of columns had a residence time of 30-d in the first column and the total residence time of the two pairs was 150 and 180-d, respectively. Testing showed both of these pairs had the same long-term performance. The column pairs with a 150 to 180-d residence time, which were both fed tertiary effluent, reached an effluent total organic carbon (TOC) of 1.8 mg/L. Column pairs with a 28 to 30-d residence time, which were fed tertiary, ozonated, and O3 /BAC effluent, reached effluent TOCs of 2.3, 2.1 and 1.8 mg/L respectively. In the latter, some TOC removal was shifted from the soil columns to the BAC. During the last 38 months of testing, using tertiary effluent as the source water, a series of sampling events was performed throughout the soil column system for N -nitrosodimethylamine (NDMA) and chemicals of emerging concern (CECs). NDMA was substantially reduced in all the columns, with a median value of 3 ng/L after 30-d and <2 ng/L after both 150 and 180-d. Twenty-one CECs were found in the majority of tertiary effluent samples, twelve of which were attenuated by the soil columns and the remaining were not. Chemicals found to be recalcitrant were 4-nonylphenol, acesulfame-k, carbamazepine, lidocaine, primidone, simazine, sucralose, sulfamethoxazole, and TCEP. Using excitation-emission matrix (EEM) techniques, soluble microbial products (SMP) peak characteristic of effluent organic matter (EfOM) is nearly eliminated after a 30-d hydraulic retention time (HRT) and completely eliminated in the 150/180-d samples. The intensity of the other peaks is significantly reduced as well, resulting in an EEM much like that of natural groundwater. Graphical abstract: Image 1 Highlights: Soil columns fed tertiary effluent reduced the TOC 67% with a 150-day HRT. NDMA was attenuated through soil columns by more than 99%. Soil column treatment attenuated 12 of the 21 CECs found in tertiary effluent. Soil columns were operated over four and ½ year period with tertiary effluent.